Темний сектор в космології: темна енергія на космологічних і астрофізичних масштабах - Novosyadlyj, B. (Publishing house "Academperiodika", 2019)
The properties and observational manifestations of the dynamical dark energy on the cosmological and astrophysical scales are discussed. We consider the dynamical dark energy in the form of quintessential and phantom scalar fields with different parameters of the equation of state and the effective sound speed. The evolution of the dynamical dark energy and its impact on the dynamics of expansion of the Universe, halos, and voids, and its behavior in the static gravitational fields of astrophysical objects are analyzed. The current state and possible tests designed to establish the nature of dark energy are highlighted.